Mixing or separating students by sex during PE classes? - Pereira, Ana (2018)
The aim of this study was to examine the influence of mixing and separating students by sex in the game performance, as heart rate (HR) demands and rate of perceived exertion (RPE) during 3-a-side small-sided soccer games (SSGs) performed in the context of Physical Education (PE) classes. Twelve students (6 male of 15.33±0.8 years; 1.77±0.10 m; 67.0±4.2 Kg; 21.50±2.5 Kg.m², and; 6 female of 15.00±0.0 years; 1.61±0.01 m; 53.8±9.1 Kg; 19.9±2.3 Kg.m2) performed the SSGs in two conditions: i) separated by sex and ii) mixed-sex. From single-sex to coeducation conditions results showed significant increases in female RPE and HR (14 to 16.1 and 142 to 163, respectively), but a decrease in the number of wrong passes, goals and shooting accuracy (p < 0.05: 80.5 to 15.2; 3.8 to 1.9 and 1.0 to 0.4, respectively). In the male group, only a single significant increase occurred in the total number of passes between the corresponding two conditions (p = 0.023: 12.5 to 14.1). When comparing the two gender groups in the mixed condition, we registered significantly higher values of the total number of passes and number of wrong passes in males than in females (74%), while the RPE was higher in females (p < 0.05). On the contrary, no significant differences between groups were observed in the separated conditions. These findings suggest a trend toward an increase in the perceived exercise intensity, not completely corroborated by HR data, with less technical proficiency for female students, mainly when playing against their male counterparts. PE teachers should be aware that mixing gender during foot-ball related activities may have a negative impact on female performance, which may impact their motivation and skill acquisition.